Robotic surgery - Nguyen P.T.; Lorate Shiny M.; Shankar K.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
There has been exponential development in procedures and publications based on robot-assisted concerning automated helped laparoscopic medical procedure in last decade. From many available reviews it has been seen that in many fields of surgery this technology allow to produce a safe and efficient method. This is a costly process. In gynecology the randomized controlled trials are missing, but the accessible proof proposes that in the field of gynecology the robotic surgery can decrease dismalness as it performs in high-volume centers it can be cost effective. It is necessary to provide training for safe and effective evolution in robotic surgery programs. BEIESP.